2021
DOI: 10.1097/aog.0000000000004522
|View full text |Cite|
|
Sign up to set email alerts
|

Human Papillomavirus Testing in the Last Cervical Screening Round at Age 60–64 Years

Abstract: Cervical human papillomavirus testing led to more positive screening test results and diagnoses of high-grade cervical intraepithelial lesions than cytology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
(29 reference statements)
0
3
0
Order By: Relevance
“…We suspect HPV infection rates to be much higher and a potential target for testing in this age group. In 1 study, it was demonstrated that including HPV testing led to a more than 50% detection of high-grade CIN lesions compared with testing with cytology alone, especially in the elderly 21 . Extending HPV screening beyond age 65 as a primary screening method may therefore be beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…We suspect HPV infection rates to be much higher and a potential target for testing in this age group. In 1 study, it was demonstrated that including HPV testing led to a more than 50% detection of high-grade CIN lesions compared with testing with cytology alone, especially in the elderly 21 . Extending HPV screening beyond age 65 as a primary screening method may therefore be beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…There is an error in Figure 1 in the article by McAdams and Lakshminrusimha in the January 2022 issue. 1 The abbreviation for "American College of Nurse Midwives" is incorrectly listed in the figure as "ANCM." The correct abbreviation is "ACNM.…”
Section: Management Of Placental Transfusion To Neonates After Delive...mentioning
confidence: 99%
“…The incorrect copyright information is listed in the article by Schroll et al 1 in the September 2021 issue. The correct copyright information is: “ © 2021 The Author(s).…”
mentioning
confidence: 99%